2015
DOI: 10.1007/s11467-014-0446-9
|View full text |Cite
|
Sign up to set email alerts
|

Quasiparticle scattering interference in the renormalized Hubbard model

Abstract: The quasiparticle scattering interference phenomenon is studied in the presence of a single impurity within the renormalized Hubbard model. By calculation of the energy and momentum dependence of the Fourier transformed local density of states in the full Brillouin zone, the main features of the quasiparticle scattering interference phenomenon in cuprate superconductors can be described qualitatively by a single point-like impurity. In particular, it is shown that with increasing energy ,the position of the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…In particular, the self-consistent parameter ∆ describes the magnitude of the pseudogap. In our previous work, 33,34 it is shown that ∆ (then the pseudogap) is particularly large in underdoped region, and then smoothly decreases with increasing doping concentration in the whole doping range from underdoped to heavily overdoped region. …”
Section: Theoretical Frameworkmentioning
confidence: 92%
See 3 more Smart Citations
“…In particular, the self-consistent parameter ∆ describes the magnitude of the pseudogap. In our previous work, 33,34 it is shown that ∆ (then the pseudogap) is particularly large in underdoped region, and then smoothly decreases with increasing doping concentration in the whole doping range from underdoped to heavily overdoped region. …”
Section: Theoretical Frameworkmentioning
confidence: 92%
“…However, it is very hard to solve this strong electron-electron interaction problem in analytic approach. In order to deal with the local constraint, the Gutzwiller renormalization factors g t and g s are introduced to rewrite the t-J model as 31,[33][34][35] …”
Section: Theoretical Frameworkmentioning
confidence: 99%
See 2 more Smart Citations